Receipt of COVID-19 and seasonal influenza vaccines in California (USA) during the 2021–2022 influenza season. Issue 6 (3rd February 2023) - Andrejko, Kristin L.; Myers, Jennifer F.; Openshaw, John; Fukui, Nozomi; Li, Sophia; Watt, James P.; Murray, Erin L.; Hoover, Cora; Lewnard, Joseph A.; Jain, Seema; Pry, Jake M.; ,
Abstract: Background: Despite lower circulation of influenza virus throughout 2020–2022 during the COVID-19 pandemic, seasonal influenza vaccination has remained a primary tool to reduce influenza-associated illness and death. The relationship between the decision to receive a COVID-19 vaccine and/or an influenza vaccine is not well understood. Methods: We assessed predictors of receipt of 2021–2022 influenza vaccine in a secondary analysis of data from a case-control study enrolling individuals who received SARS-CoV-2 testing. We used mixed effects logistic regression to estimate factors associated with receipt of seasonal influenza vaccine. We also constructed multinomial adjusted marginal probability models of being vaccinated for COVID-19 only, seasonal influenza only, or both as compared with receipt of neither vaccination. Results: Among 1261 eligible participants recruited between 22 October 2021–22 June 2022, 43% (545) were vaccinated with both seasonal influenza vaccine and >1 dose of a COVID-19 vaccine, 34% (426) received >1 dose of a COVID-19 vaccine only, 4% (49) received seasonal influenza vaccine only, and 19% (241) received neither vaccine. Receipt of >1 COVID-19 vaccine dose was associated with seasonal influenza vaccination (adjusted odds ratio [aOR]: 3.72; 95% confidence interval [CI]: 2.15–6.43); this association was stronger among participants receiving >1 COVID-19 booster dose (aOR = 16.50 [10.10–26.97]). Compared with participants testing negative for SARS- CoV-2 infection, participants testing positive had lower odds of receipt of 2021-2022 seasonal influenza vaccine (aOR = 0.64 [0.50–0.82]). Conclusions: Recipients of a COVID-19 vaccine were more likely to receive seasonal influenza vaccine during the 2021–2022 season. Factors associated with individuals' likelihood of receiving COVID-19 and seasonal influenza vaccines will be important to account for in future studies of vaccine effectiveness against both conditions. Participants who tested positive for SARS-CoV-2 in our sample were less likely to have received seasonal influenza vaccine, suggesting an opportunity to offer influenza vaccination before or after a COVID-19 diagnosis.